Elucidation of the inhibitory potential of flavonoids against PKP1 protein in non-small cell lung cancer: Inhibitory potential of flavonoids against PKP1 protein - Pandey, Pratibha; Khan, Fahad; Chauhan, Prashant; Upadhyay, Tarun Kumar; Bardakci, Fevzi; Alam, Md Jahoor; Almuzaini, Nujud; Abdalla, Rania Abdeen Hussain; Singh, Sujeet Kumar; Saeed, Mohd (Cellular and Molecular Biology, 2022)
PKP1 has been crucially involved in enhancing the MYC translation leading to lung carcinogenesis via evading numerous tumour-suppressing checkpoint systems. Plakophilin 1(PKP1) is the part of armadillo and plakophilin gene families and it is a necessary component of desmosomes. Several researches reported PKP1 protein as one of the most overexpressed proteins in human lung cancer. Therefore, we have designed our research towards elucidating better plant-based compounds as drug candidates for the management of lung cancer with minimal adverse effects over other chemotherapeutic drugs such as afatinib. This study comprises forty-six flavonoids for targeting PKP1 using in silico approaches that were not used earlier as an anti-cancerous agent targeting PKP1 in lung cancer treatment. Flavonoids are plant-derived natural compounds that exhibited enormous anti-cancerous potential against several human cancers. NPACT database was used to screen potent flavonoids that have not been used to target the PKP1 protein in lung cancer. Patch Dock and CB Dock were employed to elucidate the PKP1 (1XM9) inhibitory potential of selected flavonoids. Analysis with both the docking tools has revealed that calyxins I showed maximum affinity in comparison to the standard drug, afatinib. Further PASS and BAS analyses were performed using SWISS ADME and molinspiration to investigate the pharmacokinetic profiling of potent flavonoids having significant binding energy. Visualization of complexes was done by using UCSF chimera. However, further detailed in vitro studies are needed to validate the candidature of calyxinsI for being developed as an anticancer drug for the management of lung cancer.